COMPARISON OF INCREASE IN MUSCLE STRENGTH TRAINING INDVÍDUOS THAT TWO AND THREE TIMES A WEEK, AFTER 16 SESSIONS OF STRENGTH TRAINING. (Fiep Bulletin - online, 2013)
Strength training is now seen as an important means to achieve significant gains in strength. It is known that various benefits can be achieved with training, but it is seen that many do not have the time to practice guided by the minimum current literature. Using the justification that some individuals could decrease the weekly practice sessions, the objectives of the present study was to was to increase the strength in individuals who train two or three times a week, after 16 sessions of strength training. For this study, 10 subjects were evaluated males untrained divided into two groups: Group 1 (G2X) that exercise performed twice per week, the second group (G3X) in which trained three times a week, both with the same weekly training volume. Tests were applied to define and load the subjects followed a training program. The exercises were chosen bench press, leg press, pull, leg extension, development, leg curl, biceps, abdominal and triceps. The evaluation was done only in bench press and leg press exercises. Describing data with measures of central tendency and dispersion, it was seen that there were no changes between groups. It was concluded that probably there was no differences between those who train only twice per week and who train three times. Thus we assume that there might be a fitness training, using short training frequencies to achieve the same results in higher frequencies.
Keywords: strength training; untrained individuals; Weekly frequency